2020
DOI: 10.3390/jcm9020494
|View full text |Cite
|
Sign up to set email alerts
|

A New Site Preparation Protocol That Supports Bone Quality Evaluation and Provides Predictable Implant Insertion Torque

Abstract: When preparing an implant site, clinicians often base their assessment of the bone on subjective tactile and visual cues. This assessment is used to plan the surgical procedure for site preparation, including how many drilling steps will be used. The subjective nature of bone evaluation, consequently, results in poor reproducibility and may lead to under or over preparation of the site. Recently, an unconventional site preparation protocol was developed in which the decision of which instruments to use is dict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The system was developed based on new concepts and tools for the osteotomy to preserve bone viability. 27,28 It features a trioval conical connection with an 8 and 2. F I G U R E 2 0 Bonding of the zirconia crown on the titanium base with opaque composite resin cement following "APC" technique": Airparticle abrasion with alumina, primer application, and composite resin cement on both materials.…”
Section: Transmucosal Abutmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The system was developed based on new concepts and tools for the osteotomy to preserve bone viability. 27,28 It features a trioval conical connection with an 8 and 2. F I G U R E 2 0 Bonding of the zirconia crown on the titanium base with opaque composite resin cement following "APC" technique": Airparticle abrasion with alumina, primer application, and composite resin cement on both materials.…”
Section: Transmucosal Abutmentmentioning
confidence: 99%
“…For this specific case, a novel implant system (N1, Nobel Biocare, Zurich, Switzerland), which was optimized for immediate implant placement, was selected. The system was developed based on new concepts and tools for the osteotomy to preserve bone viability 27,28 . It features a trioval conical connection with an 8° and 2.5 mm high contact surface, creating a very strong connection and tight seal with a reduced insertion torque of 20 Ncm, 29 allowing for slim prosthetic components.…”
Section: Case Reportmentioning
confidence: 99%
“…These osseoshaping instruments are designed to create larger bone chips than conventional drills and rotate in the reverse direction when being removed from the osteotomy, which deposits the bone chips into the hole [ 10 ]. The low speed produces a temperature below that associated with osteocyte necrosis, requiring no irrigation [ 17 , 18 , 19 ], and the resultant bone coagulum contributes to bone formation, improving implant integration and stability [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of the low-speed osseoshaping tools is the ability to use these tools to evaluate the quality of the implant site based on the torque required for site preparation. A recent study [ 18 ] examining the use of the osseoshaping tools in bone surrogate materials, mini pigs, and human patients found strong, linear correlations between the torque required for site preparation using the osseoshaping instruments and both bone density and implantation torque, allowing clinicians to evaluate the implant site during site preparation, without additional assessments. A recently published clinical case series examining the use of osseoshaping instruments to place fifteen implants in seven patients found that, in most cases, the entire procedure could be completed in only three steps: pilot drilling, osseoshaping tool use, and implant insertion [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Innovation in implant dentistry includes methods, comprising both surgical [14] and prosthetic preparation techniques [15,16], post-operative interventions to increase implant stability [17], or new methods of measuring peri-implant bone [18], aiming to increase the probability of success in the long term. Innovation in implant dentistry also includes new materials and surface treatments.…”
mentioning
confidence: 99%